The phenomenon of gray economy in Poland – causes, effects andreduction methods - Franciszkowska, Sara; Węgrzyn, Anna (Journal of Finance and Financial Law, 2019)
This article deals with general issue of unofficial economy, understood as any sort of attempts made to avoid the responsibility of paying taxes by the citizens. This phenomenon is inherent on every economy and can influence it in the positive and negative way, but unfortunately the negative impact is more significant. Taking this into the consideration, the government undertakes a variety of actions to decrease the range of the gray economy. The most essential element, which affects the process of shaping the scale of the gray zone, is whether the citizens express a „silent consent” to these types of activities. This essay contains research on the level of tax morality among randomly chosen group of people, who are in their production age.